TI_GERICHTE 52.2018.258 vom 18. April 2018 , Licenza edilizia per la ristrutturazione e l'ampliamento di un edificio - TI Tribunale d'appello (2018)
Licenza edilizia per la ristrutturazione e l'ampliamento di un edificio